Behaviour of telocytes during physiopathological activation. (July 2016) - Díaz-Flores, Lucio; Gutiérrez, Ricardo; Díaz-Flores, Lucio; Goméz, Miriam González; Sáez, Francisco J.; Madrid, Juan F.
Abstract: We consider CD34+ stromal cells/telocytes (CD34+ SC/TCs) in normal and pathological conditions. These cells are involved in organisation and control of the extracellular matrix, structural support, creation of microenvironments, intercellular communication, neurotransmission, immunomodulation and immunosurveillance, inhibition of apoptosis, and control, regulation and source of other cell types. CD34+ SC/TCs are widely reported in the origin of interstitial cells of Cajal and in regeneration in the heart, skeletal muscle, skin, respiratory tree, liver, urinary system and the eye. In addition, we contribute CD34+ SC/TC hyperplasia associated with several processes, including neurogenous hyperplasia (neuroma of the appendix), hyperplasia of Leydig cells in undescended testes (Cryptorchidism), peripheral areas of inflammatory/repair processes (pericicatricial tissue and transitional zones between diseased segments in Crohn's disease and normal bowel), benign tumours (neurofibromas, Antoni-B zones of neurilemmomas, granular cell tumours, and melanocytic nevi) and in some lesions with myxoid, oedematous and degenerative changes (Reinke's oedema, myxomatous mitral valve degeneration, thyroid-associated ophthalmopathy and basophilic degenerative changes of the collagen in the dermis). We pay particular attention to the role of CD34+ SC/TCs during repair through granulation tissue, including morphologic changes, loss of CD34 expression and gain of αSMA expression with myofibroblast transformation, and interactions with pericytes, endothelial and inflammatory cells. Finally, we consider CD34 or αSMA expression in stromal cells of malignant epithelial tumours, and the role of CD34+ SC/TCs in the origin of carcinoma-associated fibroblasts (CAFs) and myofibroblasts. In conclusion, CD34+ SC/TCs play an important role in the maintenance and modulation of tissue homeostasis and in morphogenesis/renewal/repair.